Salivary Protein Components and Oral Health in Patients Undergoing Therapy with Beta Adrenegic Agonist and Antagonist - Tahani A Al-Sandook; Fayhaa AM Al-Mashhadane; Amer Taqa (University of Mosul, College of Dentistry, 2008)
Aims: To study the effect of Beta-adrenergic agonist (salbutamol) and Beta adrenergic antagonist (atenolol) on salivary protein concentration and to study relation between salivary protein concentration and oral health. Materials and Methods: This study was carried out on 45 individuals; 15 individuals of them were apparently healthy with no history of systemic diseases and represent a control group, the second group which comprised 15 subjects were given adrenergic agonist drug (salbutamol) for treatment of asthma, and third group (15 individuals) were given adrenegic antagonist drug (atenolol) for treatment of hypertension. subjects were selected from the out patients attending Oral Surgery Department, College of Dentistry, University of Mosul. The samples of saliva were collected using spitting method and oral hygiene index simplified was recorded for each individual and total protein concentration of these saliva samples were determined. Its relation to oral health was measured according to simplified oral hygiene index by Greene and Vermillion. Results: The results of this study revealed that in all study groups, significant differences were present for both salivary protein concentration and oral health scores and there is correlation between salivary protein concentration and oral health in patients receiving atenolol. Conclusions: Chronic treatment with adrenergic agonist and antagonist drugs, resulted in changes in salivary protein concentration and those will affect the oral health of patients treated by these drugs.